Passionate Intelligence Imagination and Reason in the Work of Samuel Johnson - Sachs, Arieh (Johns Hopkins University Press, 2019)
Originally published in 1967. Professor Sachs shows the inner coherence of Samuel Johnson's thought by pointing out the interconnectedness of his remarks on religious, moral, aesthetic, political, and psychological subjects. Reason and imagination, the central concepts in the Johnsonian ethos, are elucidated with reference to "vacuity," "attention," "novelty," "diversity," and other words to which Johnson attached special significance. Johnson emerges as an original thinker of the English Christian-humanist heritage; he "is to be read in the same spirit as Pascal." Primarily concerned with the relation between Johnson's ideas and the long tradition of which they are the culmination, Sachs also emphasizes the relevance of Johnson's thought to the twentieth century.